Characterization of memory T cell subsets and common γ−chain cytokines in convalescent COVID‐19 individuals. Issue 1 (8th March 2022) - Rajamanickam, Anuradha; Pavan Kumar, Nathella; Pandiaraj, Arul Nancy; Selvaraj, Nandhini; Munisankar, Saravanan; Renji, Rachel Mariam; Venkataramani, Vijayalakshmi; Murhekar, Manoj; Thangaraj, Jeromie Wesley Vivian; Muthusamy, Santhosh Kumar; Chethrapilly Purushothaman, Girish Kumar; Bhatnagar, Tarun; et al.
Abstract: T cells are thought to be an important correlates of protection against SARS‐CoV2 infection. However, the composition of T cell subsets in convalescent individuals of SARS‐CoV2 infection has not been well studied. The authors determined the lymphocyte absolute counts, the frequency of memory T cell subsets, and the plasma levels of common γ−chain in 7 groups of COVID‐19 individuals, based on days since RT‐PCR confirmation of SARS‐CoV‐2 infection. The data show that both absolute counts and frequencies of lymphocytes as well as, the frequencies of CD4 + central and effector memory cells increased, and the frequencies of CD4 + naïve T cells, transitional memory, stem cell memory T cells, and regulatory cells decreased from Days 15–30 to Days 61–90 and plateaued thereafter. In addition, the frequencies of CD8 + central memory, effector, and terminal effector memory T cells increased, and the frequencies of CD8 + naïve cells, transitional memory, and stem cell memory T cells decreased from Days 15–30 to Days 61–90 and plateaued thereafter. The plasma levels of IL‐2, IL‐7, IL‐15, and IL‐21—common γc cytokines started decreasing from Days 15–30 till Days 151–180. Severe COVID‐19 patients exhibit decreased levels of lymphocyte counts and frequencies, higher frequencies of naïve cells, regulatory T cells, lower frequencies of central memory, effector memory, and stem cell memory, and elevated plasma levels of IL‐2, IL‐7, IL‐15, and IL‐21. Finally, there was a significant correlation between memory T cell subsets and common γc cytokines. Thus, the study provides evidence of alterations in lymphocyte counts, memory T cell subset frequencies, and common γ−chain cytokines in convalescent COVID‐19 individuals. Graphical Abstract: Our study provides evidence of alterations in lymphocyte counts, memory T cell subset frequencies and common γ‐chain cytokines in convalescent COVID‐19 individuals.